2018
DOI: 10.1111/1365-2664.13151
|View full text |Cite
|
Sign up to set email alerts
|

Related plant species respond similarly to chronic anthropogenic disturbance: Implications for conservation decision‐making

Abstract: Many developing countries harbour large numbers of species that face little‐understood, gradual changes in their environment, including chronic anthropogenic disturbance (CAD), a high frequency but low intensity form of disturbance. These countries also lack the resources to study each species, so conservation practices have been generalized, assuming that complete taxonomic groups may be managed in the same ways. This approach could be justified if closely related species respond similarly to threats. We asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…As consequence, chronic disturbances and water availability show similar impact on both taxonomic and phylogenetic β-diversity. Other studies have also found similar responses to chronic disturbances and water deficit in phylogenetically related species (Martínez-Blancas et al 2018;Aguirre-Gutiérrez et al 2020). The importance of water availability for plant assemblages is known to be positively related to plant species richness (Francis and Currie 2003;Hawkins et al 2003).…”
Section: Discussionsupporting
confidence: 57%
“…As consequence, chronic disturbances and water availability show similar impact on both taxonomic and phylogenetic β-diversity. Other studies have also found similar responses to chronic disturbances and water deficit in phylogenetically related species (Martínez-Blancas et al 2018;Aguirre-Gutiérrez et al 2020). The importance of water availability for plant assemblages is known to be positively related to plant species richness (Francis and Currie 2003;Hawkins et al 2003).…”
Section: Discussionsupporting
confidence: 57%
“…However, there should be a point where human induced changes may decrease local diversity beyond natural levels by combined local extinctions and less likely colonizations through a disturbed matrix (e.g. [ 3 , 75 ]). Thus, in landscapes where most species are sensitive to ongoing disturbances, species losses are likely to overcome arrivals of tolerant species.…”
Section: Discussionmentioning
confidence: 99%
“…Adjacent to the 0.5‐ha plot of three of the sites, there was an additional 0.5‐ha plot where livestock had been excluded since 2001 using electrified fences, altogether resulting in 25 0.5‐ha plots (22 unfenced plus three fenced 0.5‐ha exclosure plots). Data on grazing intensity were already available for these plots (Martínez‐Blancas et al, 2018). Sites were selected by isolation, so that even when distance between them was small, a geographic barrier such as a ravine would separate them.…”
Section: Methodsmentioning
confidence: 99%